Penerapan Metode Single Exponential Smoothing Untuk Prediksi Penjualan Bahan Bangunan - Komariah Komariah; Edi Kurniawan; Masitah Handayani (Building of Informatics, Technology and Science (BITS), 2022)
UD. Karya Mandiri is a business engaged in the sale of goods, especially building materials contained in the Main Asahan Chart. As for UD. Karya Mandiri sells special building materials such as coconut wood, zinc, iron, nails, wall paint, wood, brickwork, ceramics and others. Based on sales data at UD. Karya Mandiri experienced an increase or decrease in sales every month. This makes UD. Karya Mandiri has a problem in controlling the inventory of building materials that cannot be predicted properly because it only calculates directly the amount of building materials left in the warehouse and then reports it to the owner and then orders the amount of building material inventory based on conventional assumptions. To avoid and reduce the level of loss in sales of building materials in the future, UD. Karya Mandiri needs a sales forecasting system. This forecasting method is Single Exponential Smoothing (SES), which can estimate sales over time with sales forecasts and request. The results of the final study that this system can predict the amount of building materials, namely in the July 2022 period broti sales 2177.18 (kg) MAPE value 15.41%, wood 2864.10 (kg) MAPE value 9.33%, zinc 532.16 ( kg) the MAPE value is 14.54% and the nail is 435.69, the MAPE value is 15.91%